Dimitriy Rostovsky reading menologion between Kyiv, Moscow and Rila monastery: A page of the history of slavonic editing and establishing a comprehensive publishing process in the Russian Empire in the 18th century - Vasil Zagorov; Gabriela Angelova (Knygotyra)
The article focuses on proofreading copies of Dimitriy Rostovskyi’s well-known Reading Menologion Lives of the Saints from the library of the biggest Bulgarian monastery – Rila Monastery. The Lives of the Saints was initially printed in the Kyiv-Pechersk Lavra, then went under the Most Holy Governing Synod’s patronage in Moscow, and was published there in 1756-9. The Rila Monastery copies contain proofreading marks, and a detailed study shows that they represent the final stage of the editorial and publishing process of the first Moscow edition. The study of Rila Library Menologion copies highlights an important issue from the book history of Eastern Europe.